2008
DOI: 10.1021/bc800265w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroelectrochemistry of N-Cobaltacarborane Porphyrin Conjugates

Abstract: N-Substituted porphyrins are well known for the distortion they exhibit of the porphyrin plane through the sp3 hybridization of one of the pyrrolenic units. They have served as model compounds in investigations of many biochemical processes. In this paper, we developed an efficient route to N-substituted porphyrins, and report the synthesis of a series of new N-substituted cobaltacarborane-porphyrins containing one or two cobaltabisdicarbollide anions linked by (CH2CH2O)2 chains to either the core porphyrin ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It is obvious that the second system can not be assigned to the reduction of Co(II) to Co(I), as this process is observed at much more negative potentials, below −2.0 V vs SCE. Moreover, the Co(III)/Co(II) process of the unsubstituted cobaltabisdicarbollide is characterized by a single reversible wave at E °′= −1.34 V vs SCE (8, 51). In the case of our study, the presence of two closely spaced systems is directly connected to the presence of the 2-oligothienyl substituents.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the second system can not be assigned to the reduction of Co(II) to Co(I), as this process is observed at much more negative potentials, below −2.0 V vs SCE. Moreover, the Co(III)/Co(II) process of the unsubstituted cobaltabisdicarbollide is characterized by a single reversible wave at E °′= −1.34 V vs SCE (8, 51). In the case of our study, the presence of two closely spaced systems is directly connected to the presence of the 2-oligothienyl substituents.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the parentc obalt bis(dicarbollide) andi ts derivatives demonstrate amphiphilic behavior and are able to self-association and micellization in solution. [63] The ring-opening of the 1,4-dioxane derivativeo fc obalt bis-(dicarbollide) with amines hasb een used earlier for synthesis of various biologically active boron containingm olecules including amino acids, [64] synthetic [65] and natural [66] porphyrins, etc. In this study we found that the 1,4-dioxane derivative of cobaltb is(dicarbollide)…”
Section: Synthesismentioning
confidence: 99%
“…Mainly, we [19] and others [20] have reported the synthesis of several conjugates of COSAN derivatives with organic fluorescent dyes (e.g. porphyrin, [20a–c] phtalocyanine, [20d, e] fluorescein, [20f] BODIPY [19b] ), essentially aiming to improve their solubility, cellular uptake and intracellular boron release for theranostic applications that combine fluorescence diagnosis with anticancer boron neutron capture therapy. In none of these cases, however, the photoluminescence properties of the fluorophores benefited from the presence of nearby metallacarborane clusters, which mainly cause a decrease of the fluorescence efficiency, [19, 20] and, to the best of our knowledge, no externally‐controlled switchable fluorescence behaviour was described for any of them.…”
Section: Introductionmentioning
confidence: 99%